Manifestações homofóbicas em espaços públicos: praças da Gentilândia em Fortaleza - Viana, Waldiane Sampaio (2009)
The main goal of this work is to understand the homosexuality behavior experienced by the people who used to walk around or lived next to the squares of Gentilândia and also to study the conflicting practices found in these areas. In this work, the homophobic demonstrations occurred in these squares and the resistance of the young people imposed against these practices in order to guarantee their space in there squares are investigated. Not so far ago, these squares were considered one of the main points of the homosexual people in Fortaleza. The conflict presented among the homosexual young people, the local resident people and other visitors is investigated, taking into account two distinct time interval in order to better understand the exposed problem. The first time interval occurred between December of 2004 until July of 2006, and the second interval between April of 2007 and August of 2008. In this scenario, it is discussed prejudice against homosexuals, the production and reproduction, as well as the process of the breakdown of this same prejudices, presented both in the Square of Gentilândia as social environment.